Conducting a survey : the SPSS workbook - McCormack, Brenda; Hill, Elizabeth (London : International Thomson Press, 1997)
Introduction. The survey process. Selecting a sample. Questionnaire design for SPSS. Administering a survey. Data summary and descriptive statistics. Data analysis...
Keywords: Methodology; Social sciences; Computer file; SPSS; Social sciences -- Methodology; Social sciences -- Statistical methods -- Computer programs; SPSS (Computer file); Social surveys